The Partial Credit Model applied to the Lie Scale of the Big Five Questionnaire - Abal, Facundo Juan Pablo (2017)
The Partial Credit Model (PCM) of the Item Response Theory was applied to the Spanish Lie Scale adaptation of the Big Five Questionnaire. The scale measures individuals’ tendency to provide a distorted profile. The sample comprised 1592 adults from the general population (55% females). All analyses were performed by means of Winsteps software. The PCM exhibited satisfactory goodness-of-fit for all items. However, a considerable proportion of respondents had incongruent response patterns which were not in agreement with the model’s expectations. Five items presented inversions in the order expected for the estimated values of threshold parameters. These findings show the scale weaknesses and yield useful information to guide possible changes in future research.